Cerebral Palsy Types Based on Kind of Disability Correlated with The Functional Independence - Bambang Trisnowiyanto; Isna Andriani (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
Cerebral palsy is a collection of motor disorders caused by brain damage that occur before, during or after birth which can be caused by many factors such as, congenital, genetic, inflation, infection and poisoning during pregnancy, trauma and metabolic disorders. Children with cerebral palsy will mostly have problems with posture. Therefore, to find out the level of independence in children with cerebral palsy, it is necessary to have an examination carried out by health workers, especially physiotherapy. The purpose of this study was to determine the prevalence of the most common type of CP that occurred in CP events which were correlated with the level of activities functional independence of the child's movements. This research was an observational descriptive study with a measuring instrument for the Gross Motor Function Classification System Expanded and Resived. Based on the analysis of the data obtained in the independent category of 33 children (6,3%) with quadriplegia spastic CP type, 34 children (6,5%) with diplegia spastic CP type, 15 children (2,9%) with spastic hemiplegia CP type , 19 children (3,6%) with atetoid CP type, and 28 children (5,4%) with hyponia CP type. On the other hands, in the dependent category there were 149 children (28,5%) with quadriplegia spastic CP type, 156 children (29,8%) with diplegia spastic CP type, 18 children (3,4%) with spastic hemiplegia CP type, 27 children (5,2%) with atetoid CP type, and 44 children (8,4%) with hyponia CP type. Conclusion the type of CP that has the highest prevalence was spastic group CP with a low or dependent level of independence, and correlates perfectly (+1) between the types of cerebral palsy with the level of functional independence of children based on pearson product moment.